Drying Cocoa - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
A picture of a group of workers beginning the process of spreading the cocoa beans on a cocoa house.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa houses